TMEM41B is a novel regulator of autophagy and lipid mobilization. (20th August 2018) - Moretti, Francesca; Bergman, Phil; Dodgson, Stacie; Marcellin, David; Claerr, Isabelle; Goodwin, Jonathan M; DeJesus, Rowena; Kang, Zhao; Antczak, Christophe; Begue, Damien; Bonenfant, Debora; Graff, Alexandra; et al.
Abstract: Autophagy maintains cellular homeostasis by targeting damaged organelles, pathogens, or misfolded protein aggregates for lysosomal degradation. The autophagic process is initiated by the formation of autophagosomes, which can selectively enclose cargo via autophagy cargo receptors. A machinery of well‐characterized autophagy‐related proteins orchestrates the biogenesis of autophagosomes; however, the origin of the required membranes is incompletely understood. Here, we have applied sensitized pooled CRISPR screens and identify the uncharacterized transmembrane protein TMEM41B as a novel regulator of autophagy. In the absence of TMEM41B, autophagosome biogenesis is stalled, LC3 accumulates at WIPI2‐ and DFCP1‐positive isolation membranes, and lysosomal flux of autophagy cargo receptors and intracellular bacteria is impaired. In addition to defective autophagy, TMEM41B knockout cells display significantly enlarged lipid droplets and reduced mobilization and β‐oxidation of fatty acids. Immunostaining and interaction proteomics data suggest that TMEM41B localizes to the endoplasmic reticulum (ER). Taken together, we propose that TMEM41B is a novel ER‐localized regulator of autophagosome biogenesis and lipid mobilization. Synopsis: Autophagy maintains cellular homeostasis by targeting damaged organelles, pathogens or misfolded proteins for lysosomal degradation. The ER transmembrane protein TMEM41B is a novel regulator of autophagosome biogenesis, lipid droplet homeostasis and mitochondrial respiration. TMEM41B localizes to the endoplasmic reticulum. Knockout of TMEM41B impairs autophagosome biogenesis and lysosomal delivery of cargo. Absence of TMEM41B results in enlarged lipid droplets. TMEM41B is required for mobilization and mitochondrial β‐oxidation of fatty acids. Abstract : Autophagy maintains cellular homeostasis by targeting damaged organelles, pathogens or misfolded proteins for lysosomal degradation. The ER transmembrane protein TMEM41B is a novel regulator of autophagosome biogenesis, lipid droplet homeostasis and mitochondrial respiration.